Two-dimensional laminates in monoclinic-II modulated martensites. (15th June 2021) - Seiner, Hanuš
Abstract: Mathematical theory of martensitic microstructures is used to study the set of energy-minimizing laminates forming in shape memory alloys undergoing cubic-to-monoclinic-II transitions, where the monoclinic-II structure is an approximation of modulated martensite having a 〈110〉 P -oriented modulation vector. In particular, the twinning systems that do not change the orientation of the c -axis (i.e. the in-plane twinning modes) are analyzed. A numerical procedure is used to calculate the set of all energy minimizers, i.e. the quasi-convex hull, utilizing the theoretical finding by Bhattacharya and Dolzmann (2001) that this set can be fully covered by laminates of no higher order than the second. The results are discussed with respect to the experimentally observed microstructures in 10 M Ni-Mn-Ga martensite.